Navigating The Landscape Of Innovation & Entrepreneurship In Pakistan: A Review - Muhammad Iftikhar Hanif; Asif Maqsood Butt; Omaima Asif (Journal of Rawalpindi Medical College)
This article's abstract explores the concepts of innovation and entrepreneurship and how they work together to promote economic progress. Despite its challenges, Pakistan may prosper in these fields thanks to its large and growing market, skilled labour force, and supportive political environment. However, for innovation and entrepreneurship to live up to their potential, several problems need to be resolved, including bureaucracy and corruption, poor intellectual property protection, inadequate research and development, and limited access to capital.